Role of Glutathione in Male Infertility (Bangladesh Journal of Medical Biochemistry, 2013)
Infertility is a worldwide problem and in almost 50% of cases infertility results from abnormality of the male partners. Apart from endocrine disorders, definitive cause and mechanism of male infertility is not clear in many cases. Recent evidence indicates that imbalance between pro-oxidant stress and antioxidant defense plays an important role in the pathogenesis of male infertility. Among the endogenous antioxidant systems, reduced glutathione (GSH) plays a significant role in the antioxidant defense of the spermatogenic epithelium, the epididymis and perhaps in the ejaculated spermatozoa. The current study was therefore designed to evaluate any association that may exist between GSH levels and male infertility. Infertile male patients (having female partners with normal fertility parameters; n=31) and age- matched healthy male fertile control subjects (n=30) were included in this study. In addition to medical history, semen analyses including semen volume, sperm count, motility and morphology were done for each subject. As a measure of antioxidant capacity erythrocyte and seminal plasma GSH concentrations were measured by Ellman's method in fertile and infertile male subjects. The infertile subjects were similar to fertile subjects in terms of age. However, semen volume and sperm count was found significantly lower (p